Anemia among children and adolescents in a rural area - Ivan Riyanto Widjaja; Felix Firyanto Widjaja; Lucyana Alim Santoso; Erick Wonggokusuma; Oktaviati Oktaviati (Indonesian Pediatric Society, 2014)
Background Anemia in children and adolescents affects growthand development. It is a preventable disease, but unfortunately isoften ignored until the symptoms occur. There have been limitedreports on the prevalence of anemia in children and adolescentsin Indonesia, especially from rural areas.Objective To describe the prevalence of anemia in children andadolescents in district ofMalinau, a rural area in East KalimantanProvince.Methods This cross-sectional study was done in June 20 10 usinglaboratory records between July 2009 to January 20 10. Laboratoryrecords of patients aged between 6 months and 18 years whichinvestigated were complete blood count (CBC) from ambulatory,inpatient, and emergency care ofMalinau Public Hospital in EastKalimantan. Mentzer and England & Fraser indices were used todifferentiate iron deficiency anemia (IDA) and thalassemia amongmicrocytic hypochromic anemic patients.Results This study involved 709 laboratory records. Prevalenceof anemia was 53 .9% (95% CI 50.2% to 57 .5%) . The prevalenceof IDA among age groups were as follows: 29.4% (95% CI 24.3to 34.5%) in 6- 59 months group, 16% (95% CI 11 to 21 %) in5- 11.9 years, and 15.2% (95% CI 10.2 to 20.2%) in 12- 18 years.Children aged 6- 59 months tended to have more anemia th anthose aged 5- 11.9 years (OR 2. 184, 95% CI 1.398 to 3.413) oraged 12- 18 years (OR 2.3 19, 95% CI 1.464 to 3.674).Conclusion T he prevalence of an emia in children andadolescents of the Malinau Regency is 53 .9% (95% CI 50.2 to57.5%), quite similar to that of other developing countries . Agovernment program to overcome anemia is recommended, n otonly for pregnant women, but also for children and adolescents.